Effects of Hippeastrum reticulatum on memory, spatial learning and object recognition in a scopolamine-induced animal model of Alzheimer's disease - Trang Huyen Xuan Hoang; Duc Viet Ho; Kiem Van Phan; Quan Van Le; Ain Raal; Hoai Thi Nguyen (Taylor & Francis Group, 2020)
Context The methanol extracts from Hippeastrum reticulatum (L'Hér.) Herb. (Amaryllidaceae) (HR) display acetylcholinesterase inhibitory (AChEI) activity. Objective AChEI of alkaloids isolated from HR bulbs and the ameliorating effects of the alkaloid fraction (AHR) on memory and cognitive dysfunction in scopolamine-treated mice were investigated. Materials and methods Alkaloids were isolated by column chromatography and identified by spectroscopy. AChEI was evaluated using the modified Ellman's method. Sixty Swiss male mice were randomly divided into six groups, received samples for 15 days. Normal group received saline, scopolamine-treated group scopolamine (1.5 mg/kg, intraperitoneal injection). Test groups received AHR (5, 10 and 15 mg/kg, per os) and positive control group donepezil (5 mg/kg, per os), administered 1 h before the test, scopolamine was injected 30 min prior to testing. The cognitive-enhancing activity of AHR against scopolamine-induced memory impairments was investigated using Y-maze, the novel object recognition test (NORT) and the Morris water maze (MWM) test. Results Seven alkaloids were isolated for the first time from the genus Hippeastrum: trans-dihydronarciclasine (1), N-chloromethylnarcissidinium (2), narciprimin (3), narciclasine-4-O-β-d-xylopyranoside (4), N-methyltyramine (5), 3β,11α-dihydroxy-1,2-dehydrocrinane (6) and brunsvigine (7); three are new compounds (2, 5, 6). Among them, 2-3 and 5-6 showed AChEI in vitro with IC50 values of 29.1, 46.4, 70.1 and 104.5 µg/mL, respectively. The anti-AChEI of 2, 5 and 6 are reported for the first time. In in vivo test, AHR (15 mg/kg) significantly increased in spontaneous alternation performance in the Y-maze test (p < 0.01), it significantly increased the time spent exploring the novel object (p < 0.05) comparison with scopolamine-treated group. The administration of AHR at doses 10 and 15 mg/kg significantly decreased escapes latency and swimming distance to the platform on day 6 compared to these in day 1 (p < 0.01 and p < 0.05, respectively). Conclusions AHR could be a potential candidate of future trials for treatment of memory and cognitive dysfunction in Alzheimer's disease.